PGA data of Antarctic carbonaceous chondrites with CI and CM affinity - Ebihara, M (via Mendeley Data) (2024)
At present, carbonaceous chondrites are classified into nine groups based on their chemical characteristics. Among carbonaceous chondrites, CI and CM chondrites are considered the more primitive meteorites. Currently, there are five known non-Antarctic CI chondrites, and four have been identified among Antarctic meteorites. In this study, elemental analysis was conducted on a total of twelve meteorites, focusing primarily on the major element composition, including four Antarctic CI chondrites and eight others having affinities with CI or CM but insufficiently chemically clarified. The analytical method employed in this study was neutron-induced prompt gamma-ray analysis (PGA), which shares analytical advantages similar to wet chemical analysis. Quantitative values were obtained for 15 elements: Fe, Mg, Si, S, Ni, H, Al, Ca, Cr, Mn, Co, Ti, chlorine, B, and Gd, and almost all of the main constituent elementals were quantified. Comparison with literature values, including those obtained by the wet chemical method, confirmed that the values obtained by the PGA method in this study are sufficiently reliable with the exception of B. Oxygen isotopic compositions of five of the 12 meteorites analyzed, including the Y-86029 meteorite classified as CI, have been reported, and based on the results, a new group name CY was proposed for these meteorites. PGA analysis showed that, in common with the 12 meteorites, H and chlorine are more deplete than those in non-Antarctic CI chondrites. Notably, the degree of this depletion varies significantly between meteorites and exhibits a correlation between the two elements. Petrological and mineralogical observations suggest that these meteorites underwent thermal metamorphism after aqueous alteration on their parent body, being consistent with the observed depletion of chlorine and H. Based on these findings, it was deemed appropriate to classify the analyzed twelve meteorites as CY chondrites. Based on the abundance of Mn and S, it was revealed that these twelve meteorites are ...